Phonological Description of Teochew Dialect in Pontianak West Kalimantan - Lily Thamrin (Lingua Cultura, 2020)
The research aimed to describe the phonological system of the Pontianak Teochew dialect spoken by the Chinese community in West Kalimantan, including vocals, consonants, and tones, using descriptive method. The phonological escription in question included both phonetic and phonemic descriptions with the subject of language that objectively and accurately describes the current aspects of Teochew’s phonology. The phonetic system of the Pontianak Teochew language would be articulately identified based on the way sounds are formed by human speech tools, namely through consonants, vocals and diphthong. The research data were obtained from three Pontianak Teochew informants who used the Teochew dialect as their daily conversation language. The informants were around 70-75 years old. Based on the research results, there are 18 consonant phonemes, 88 vocal phonemes, and eight tones. The research results show that the Pontianak Teochew dialect has its own characteristics that distinguish it from the other regional Teochew dialects.